Resilience, Supply Chains and the Great Recession - Steven Brakman; Charles van Marrewijk (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyse the link between supply chains and the extent to which the Great Recession has affected national economies. Our analysis is in two steps, namely first for value added measures of supply chains and then for the Grubel-Lloyd index using gross-export data. Regarding value added measures we find, in general, no effect. Only if we separate out Europe do we find that the trough in Europe occurs about 0.17 years later and the recovery (for the countries that have recovered) about 1.55 years later. Moreover, the duration of the decline in Europe is about 4 months longer and of the recovery about 17 months longer. We explain this link and Europe's special role using a detailed Grubel-Lloyd index applied to gross-exports as an alternative supply chain measure, which significantly affects the impact of the Great Recession regarding the timing and duration of the recovery (later and longer).
Keywords: E32; R11; R12; 330; resilience; Great Recession; supply chains